2021
DOI: 10.3892/ijo.2021.5236
|View full text |Cite
|
Sign up to set email alerts
|

lncRNA HCP5 acts as a ceRNA to regulate EZH2 by sponging miR‑138‑5p in cutaneous squamous cell carcinoma

Abstract: Long non-coding RNAs (lncRNAs) and microRNAs (miRNAs) are essential for the progression of tumors, including cutaneous squamous cell carcinoma (CSCC). The present study aimed to examine the competing endogenous RNA (ceRNA) network in CSCC. Differentially expressed genes in CSCC were analyzed using the GSE66359 microarray data set, and the upstream miRNAs and lncRNAs were predicted using online database analysis (TargetScan 7.1, mirDIP 4.1, miRSearch V3.0, miRDB and RNA22 2.0) and were verified in clinical tiss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 41 publications
1
8
0
Order By: Relevance
“…In addition, HCP overexpression enhanced chemoresistance in gastric cancer and esophageal carcinoma (19,20). Besides this, HCP5 was prominently upregulated and acted as an oncogene in pancreatic cancer, bladder cancer, gastric cancer, and cutaneous squamous cell carcinoma (21)(22)(23)(24). Consistent with previous reports of other cancers, HCP5 expression was also upregulated in LSCC cells, and HCP5 was an oncogene.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…In addition, HCP overexpression enhanced chemoresistance in gastric cancer and esophageal carcinoma (19,20). Besides this, HCP5 was prominently upregulated and acted as an oncogene in pancreatic cancer, bladder cancer, gastric cancer, and cutaneous squamous cell carcinoma (21)(22)(23)(24). Consistent with previous reports of other cancers, HCP5 expression was also upregulated in LSCC cells, and HCP5 was an oncogene.…”
Section: Discussionsupporting
confidence: 89%
“…Besides this, lncRNA is elucidated to enhance the expression of targeted genes by sponging with miRNAs (33). HCP5 promotes cancer development by sponging miR-140-5p, miR −138−5p, miR-29b-3p, and miR-143-3p (21)(22)(23)(24). In addition, HCP5 can sponge miR-216a-5p in cervical cancer (34).…”
Section: Discussionmentioning
confidence: 99%
“…In order to intuitively observe the apoptosis of periodontal tissues, apoptotic cells were detected by TUNEL staining as mentioned above [ 20 ]. Processing of the sections and staining with TUNEL reactive mixture were in line with manufacturer’s instructions (Wanleibio Co., Ltd.).…”
Section: Methodsmentioning
confidence: 99%
“…As a result, increasing WWOX levels in cancer cells may be a potential method of suppressing autophagy (Tsai et al, 2013). Additionally, the most recent finding has demonstrated that inhibiting autophagy via silencing human histocompatibility leukocyte antigen complex P5 (HCP5) decreased the enhancer of zeste homolog 2 (EZ2H) expression and inhibited the STAT3/VEGFR2 pathway via competitive binding to miR-138-5p, which resulted in apoptosis in SCC cells (Zou et al, 2021).…”
Section: Autophagy In Skin Cancermentioning
confidence: 99%